Boosting the energy density of aqueous MXene‐based supercapacitor by integrating 3D conducting polymer hydrogel cathode. Issue 3 (24th April 2022) - Chu, Xiang; Wang, Yihan; Cai, Lucheng; Huang, Haichao; Xu, Zhong; Xie, Yanting; Yan, Cheng; Wang, Qing; Zhang, Haitao; Li, Hong; Yang, Weiqing
Abstract: The wide‐spread proliferation of aqueous MXene‐based supercapacitor has been largely shadowed by the limited cell potential window (typically in the range of 0–0.6 V). To address this baffling issue, designing asymmetric supercapacitor (ASC) is proposed as a rational strategy to enlarge the potential window (thus energy density) of individual cell in aqueous electrolytes. To this date, however, it still remains a great challenge to develop easy fabricating, 3D nanostructured, and pseudocapacitive cathode materials that can perfectly match with MXene anode materials. In this work, we propose a supramolecular strategy to construct conducting polymer hydrogel (CPH) with highly interconnected 3D nanostructures and large pseudocapacitance, which can finely match with 2D Ti3 C2 T x . The as‐assembled CPH//Ti3 C2 T x ASC with CPH cathode and MXene anode can operate in a broadened potential window of 1.15 V in aqueous PVA/H2 SO4 gel electrolyte with remarkably improved energy density of 16.6 μWh/cm 2 (nine times higher than that of symmetric MXene supercapacitor). Additionally, this ASC exhibits outstanding cyclic stability with no trackable performance decay over 30, 000 galvanostatic charge and discharge cycles. It is demonstrated in this work that employing positive CPH electrode is a feasible yet promising strategy to enhance the potential window and energy density of aqueous MXene supercapacitors. Abstract : The widespread application of aqueous MXene‐based supercapacitors has long been compromised due to the limited cell potential window. Herein, a 3D conducting polymer hydrogel is electrochemically constructed via crosslinking polyaniline chains, which delivers a high pseudocapacitance of 402.5 F/g against positive potential window. Therefore, the 3D conducting polymer hydrogel cathode is rationally integrated with 2D Ti3 C2 Tx MXene anode to fabricate asymmetric CPH//Ti3 C2 T x ASC that exhibits enlarged potential window of 1.15 V and boosted energy density of 16.6 μWh/cm 2 .